I am not a racist, I even have black friends: the self-defensive role of the justifications of racism - Brito, Tátila Rayane de Sampaio (2020)
Racist attitudes and behaviors have been strongly resisting the anti-racism norm. Theorizing and research on intergroup relations have shown this occurs because people use justifications to mitigate their behavior's discriminatory nature. In this respect, the literature has not yet clarified whether the simple act of justifying the racist behavior itself is sufficient to protect both the perpetrator's positive private and social image. The current thesis discusses this issue by proposing that individuals spontaneously elaborate justifications for their discriminatory behaviors against groups protected by the anti-racism norm, thus preserving their self-esteem and social image. We have developed a research program to test this hypothesis, whose results we organized into three articles. In a preliminary paper, we conducted three studies in which we assessed the validity and reliability of a self-esteem scale that we used in subsequent studies. In the second article, we conducted an exploratory study (N = 100) that showed that black people are perceived as more protected by the Brazilian context's anti-prejudice norm. In this thesis's main article, we carried out five experimental studies to test the core aspects of the proposed hypothesis. In Experiment 1 (N = 203), we show that participants accused of being racist had their implicit self-esteem affected. In Experiment 2 (N = 102), we show that the mere act of justifying racism mitigates the negative impacts on the implicit self-esteem of participants accused of racism. In Experiment 3 (N = 137), we replicated previous results in another cultural context (i.e., Spain). In Experiment 4 (N = 196), we went further by showing that the negative impact of being accused of racism occurs in managing the most egalitarian participants' social image. Experiment 5 (N = 148) analyzed the anti-prejudice norm's moderating role on the impact of being accused of racism on individuals' self-esteem. In general, the results confirm the proposed hypotheses and contribute to studies on processes that legitimize prejudice and discrimination.